Cover Image: Crystallization behavior in miscible blends of poly(ε‐caprolactone) and poly(hexylene adipate) with similar thermal properties studied by time‐resolved Fourier transform infrared spectroscopy. Issue 1 (24th March 2020) - Rohindra, David; Lata, Roselyn; Kuboyama, Keiichi; Ougizawa, Toshiaki
Crystal Morphology: In article e10037, Rohindra and colleagues report the crystallization behavior of blended Poly (ε‐caprolactone) (PCL) and Poly(hexylene adipate) (PhAd). The cover image micrograph shows the spherulites of PCL and PhAd in a blend of 20/80 ratio isothermally crystallized at 47 °C. At this crystallization temperature, morphologically similar types of spherulites were observed in the blend, although neat PCL showed large spherulites with negative birefringence while PhAd also showed negative birefringence but small spherulite size. This indicated that PhAd was acting as the nucleating agent for PCL. Because of the similarity of the spherulites, it was difficult to distinguish the two polymers by POM. The crystallization process of the two polymers in the blends was studied by time resolved FTIR spectroscopy. (DOI: 10.1002/PCR2.10037 )